Optimization of the thrombin generation test components to measure potency of factor VIII concentrates. (1st April 2016) - Jha, N. K.; Shestopal, S. A.; Gourley, M. J.; Woodle, S. A.; Liang, Y.; Sarafanov, A. G.; Weinstein, M.; Ovanesov, M. V.
Abstract : Introduction: The thrombin generation test (TGT) is used both as a global haemostasis assay, and to compare activities of coagulation factor concentrates that have been spiked into patient plasma. However, TGT has not been systematically optimized to evaluate factor VIII (FVIII) product potency. Aims: To improve the sensitivity of TGT to FVIII and allow a comparative analysis of the thrombin generating capacities of FVIII concentrates against reference preparations with known FVIII activity. Methods: Concentrations of TGT components (analytical variables) were assessed to maximize the linearity and range of responses to the concentration of FVIII. Results: We optimized the range and sensitivity of the TGT assay with respect to FVIII through the addition of FXIa to the assay. Other parameters that were adjusted, i.e. tissue factor (TF), procoagulant lipids and plasma concentrations, did not improve the ability of the assay to measure both high and very low levels of FVIII. In the optimized TF/FXIa‐activated TGT assay, all thrombin generation curve parameters were suitable for FVIII quantification, but thrombin peak height and maximal velocity demonstrated better linearity in the desired FVIII range. We found that the optimized TF/FXIa‐activated TGT has a wider range of sensitivity to FVIII than a commercially available TGT. Additionally, we demonstrated that the TF/FXIa‐activated assay performs adequately by comparing potency measurements of five commercially available FVIII products using TGT and traditional chromogenic and one‐stage clotting assays. Conclusions: The optimized TGT assay can be used to quantify and compare the thrombin generating capacities of FVIII concentrates.